Prognostic Validity of the American Joint Committee on Cancer and the European Neuroendocrine Tumors Staging Classifications for Pancreatic Neuroendocrine Tumors: A Retrospective Nationwide Multicenter Study in South Korea. Issue 7 (August 2016) - Cho, Jae Hee; Ryu, Ji Kon; Song, Si Young; Hwang, Jin-Hyeok; Lee, Dong Ki; Woo, Sang Myung; Joo, Young-Eun; Jeong, Seok; Lee, Seung-Ok; Park, Byung Kyu; Cheon, Young Koog; Han, Jimin; et al.
Abstract : Objectives: Pancreatic neuroendocrine tumors (pNETs) are diverse diseases with different prognosis. The American Joint Committee on Cancer (AJCC) and the European Neuroendocrine Tumor Society (ENETS) introduced 2 different tumor node metastasis (TNM) stages, and the World Health Organization (WHO) proposed WHO 2010 grading system for pNETs. Therefore, we aimed to validate the prognostic relevance of these 3 systems for pNETs in South Korea. Methods: The Korean Society of Gastrointestinal Cancer created a retrospective registry of pNETs in 153 patients from 15 hospitals between 2002 and 2012. Results: On the basis of the WHO 2010 grade, 2-year progression-free-survival (PFS) rates for G1, G2, and G3 were 92%, 62%, and 25% ( P < 0.01). According to ENETS and AJCC staging, 2-year PFS rates for stages I through IV were 94%, 87%, 49%, 20%, and 92%, 61%, 60%, 20%, respectively ( P < 0.01). A Cox multivariate regression analysis revealed that the only statistically significant prognostic factor was the TNM classification of either the AJCC or the ENETS stage ( P < 0.01). In addition, the κ value between the AJCC and the ENETS stages was 0.46 indicating a "moderate" agreement ( P < 0.01). Conclusions: The AJCC and ENETS TNM classifications for pNETs are prognostic for PFS and can be adopted in clinical practice in South Korea.